Activation of adenosine receptor A2A increases HSC proliferation and inhibits death and senescence by down-regulation of p53 and Rb - Ahsan, Md. Kaimul; Mehal, Wajahat Z. (Frontiers in Pharmacology, 2014)
Background & Aims: During fibrosis hepatic stellate cells (HSC) undergo activation, proliferation and senescence but the regulation of these important processes is poorly understood. The adenosine A2A receptor (A2A) is known to be present on HSC, and its activation results in liver fibrosis. In this study, we tested if A2A has a role in the regulation of HSC proliferation, apoptosis, senescence, and the relevant molecular mechanism. Methods: The ability of adenosine to regulate p53 and Rb protein levels, proliferation, apoptosis and senescence was tested in the human HSC cell line LX-2 and rat primary HSC. Results: Adenosine receptor activation down-regulates p53 and Rb protein levels, increases BrdU incorporation and increases cell survival in LX-2 cells and in primary rat HSC. These effects of NECA were reproduced by an adenosine A2A receptor specific agonist (CGS21680) and blocked by a specific antagonist (ZM241385). By day twenty-one of culture primary rat HSC entered senescence and expressed -gal which was significantly inhibited by NECA. Furthermore, NECA induced down regulation of p53 and Rb and Rac1, and decreased phosphorylation of p44-42 MAP Kinase in LX-2 cells and primary rat HSC. These effects were reproduced by the cAMP analog 8-Bromo-cAMP, and the adenylyl cyclase activator forskolin, and were blocked by PKA inhibitors. Conclusions: These results demonstrate that A2A receptor regulates a number of HSC fate decisions and induces greater HSC proliferation, reduces apoptosis and senescence by decreasing p53 and Rb through cAMP-PKA/Rac1/p38 MAPK pathway. This provides a mechanism for adenosine induced HSC regulation and liver fibrosis.